2010
DOI: 10.1097/aog.0b013e3181dd22ef
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Pregnancy and Emergency Contraceptive Pills

Abstract: Objective To evaluate the existing data to estimate the rate of ectopic pregnancy among emergency contraceptive pill treatment failures. Data Sources Our initial reference list was generated from a 2008 Cochrane review of emergency contraception. In August 2009, we searched Biosys Previews, the Cochrane Database of Systematic Reviews, Medline, Global Health Database, Health Source: Popline, and Wanfang Data (a Chinese database). Methods of Study Selection This study included data from 136 studies which fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 35 publications
3
32
1
2
Order By: Relevance
“…5 After the occurrence of a few cases of ectopic pregnancies following the failure of LNG-EC, it is recommended in several countries that in case of a conception following a failed EC with LNG, the possibility of ectopic pregnancy should be considered. 6 Although the risk of ectopic pregnancy increases with alterations in the tubal motility and ciliary dysfunction caused by LNG, in a systematic review conducted by Cleland et al, 6 ectopic pregnancy rate is reported as 1% among women exposed to LNG-EC, while the risk of ectopic pregnancy among women that did not use EC pills was 0.8 to 2%. Therefore, they concluded that risk of ectopic pregnancy after failed EC pills was not greater than the risk observed in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…5 After the occurrence of a few cases of ectopic pregnancies following the failure of LNG-EC, it is recommended in several countries that in case of a conception following a failed EC with LNG, the possibility of ectopic pregnancy should be considered. 6 Although the risk of ectopic pregnancy increases with alterations in the tubal motility and ciliary dysfunction caused by LNG, in a systematic review conducted by Cleland et al, 6 ectopic pregnancy rate is reported as 1% among women exposed to LNG-EC, while the risk of ectopic pregnancy among women that did not use EC pills was 0.8 to 2%. Therefore, they concluded that risk of ectopic pregnancy after failed EC pills was not greater than the risk observed in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Bu da LNG'nin fallop tüpü motilitesini etkilemediğinin bir göstergesidir 16 . LNG kullanımında en sık görülen yan etkiler bulantı, kusma ve irregüler vajinal kanamalardır.…”
Section: Levonorgestrel (Lng)unclassified
“…A systematic review found that when ECPs fail, the proportion of pregnancies that are ectopic does not exceed the proportion of ectopic pregnancies in the general population. 48 Like all contraceptive methods, ECPs reduce the absolute risk of ectopic pregnancy by preventing pregnancy in general.…”
Section: Safety and Contraindicationsmentioning
confidence: 99%